Imagem institucional: a percepção do público estudantil de Ensino Médio sobre o Instituto Federal de Educação, Ciência e Tecnologia do Maranhão (IFMA) - COSTA, Roberta Mouzzana Cutrim (2021)
To analyze the perception of the image of the Federal Institute of Education, Science and Technology of Maranhão – IFMA – by the student public. To achieve the proposed objective, the methodology includes bibliographic and exploratory research, a look at the Image Configuration Method, according to the perspective of Schuler and Toni (2015). The research aims to understand how the student public feels in the condition of belonging to the IFMA, in a daily affirmation of this presence that will build the institutional image. To support the investigation, we have a theoretical contribution about organizational communication, the institutional image, in dialogue with the documentary and historical-academic records of the IFMA: Institutional Development Plan and the Institutional Pedagogical Project. Theoretical-methodological arrangements lead to an understanding of the dynamics that the image perception process requires, taking into account that the framings are temporary, demanding observational care from the communication management for changes in the assessment scenario of the institute, arising from the student body. From what was found in this investigation, the IFMA translates, for the students, a perception that there are, notably, quality of teaching, search for knowledge, consolidated learning location, trained professionals; and, frequently, the offer of technical courses.